O corpo litúrgico do Estado - um ensaio sobre a disputa pela soberania - Augusto, Gabriel Luiz (Universidade Federal de São Carlos, 2017)
This thesis aims to investigate the intersection between the theological-political sphere and the subjectivation process in the modern era. Through genealogical procedures, it was intended to inquire the birth/origination of fundamental concepts in the field of contemporary theology-politics, such as sovereignty, State and bare life which are present in the late Middle Age and the beginning of modern era. That was done by analyzing how the modern State machinery and its images are structured and function through subjectivizing discourses. The analysis of the narratives of the concept of “glory”, alongside to the concept of “sovereignty”, are going to be the guiding lights of this thesis, through the perspectives that have helped to detach the concept of “sovereignty” from the traditionally conveyed images in relation to the State and to the modern legal order.
Keywords: Estado; Teologia-política; Soberania; State; Theology-politics; Sovereignty; CIENCIAS HUMANAS::EDUCACAO